3D Structure of the Juxtamembrane Domain of the Human Epidermal Growth Factor Receptor and Its Interaction with Calmodulin by NMR Spectroscopy - Kiattawee Choowongkomon; Cathleen Carlin; Frank D. Sönnichsen (Agriculture and Natural Resources, 2006)
Epidermal growth factor receptor (EGFR) is involved in the regulation of cellular proliferation and differentiation. Its juxtamembrane domain (JX), plays important roles in receptor trafficking since both basolateral sorting in polarized epithelial cells and lysosomal sorting signals are identified in this region. In order to understand the regulation of these signals, we characterized the structural properties of recombinant JX domain in dodecylphosphocholine detergent (DPC) by nuclear magnetic resonance (NMR) spectroscopy. In DPC micelles, structures derived from NMR data showed three amphipathic, helical segments. Furthermore, JX domain showed to interact with calmodulin by NMR techniques. Two binding sites of calmodulin on JX domains were identified. Our data suggested that the activity of sorting signals may be regulated by their membrane association and calmodulin binding which imply the restricted accessibility in the intact receptor.